C-Dump Converter Design and its Dynamic Analysis in Simulink Environment for a Switch Reluctance Machine - (:unkn) unknown (My University, 2019)
It is an analysis of asymmetric converters used to drive switched-reluctance motors (SRM). Usually, two switches per phase exist in these converters, therefore the cost of converter rises up. The energy recovery chopper in a capacitor-dump (C-dump) SRM drive which needs one more additional switch than the number of phases is analyzed, designed and discussed. The converter allows continuous output current operation. The dynamic behavior of the chopper shows that it operates as a boost DC-to-DC converter in a regenerative mode. In this study, A 6/4 SRM for both no motor phase current control applied and controlled at 8A phase current (C.C.), the characteristics of C-dump converter voltage (Vc), current (ig) and phase voltages applied to the motor windings are examined in Matlab-Simulink environment.